Toward a structural view of co‐opetition in supply networks. Issue 5 (16th April 2014) - Pathak, Surya D.; Wu, Zhaohui; Johnston, David
Abstract: Co‐opetition, or simultaneous competition and cooperation, in the supply chain management literature has been treated as a dyadic relational phenomenon where the buyer's strategy is considered to be the primary driver. In this paper, we move beyond the dyadic view and propose a theory of co‐opetition in supply networks. We argue that as firms within a supply network interact over time to access, share, and transform resources, new ties between firms are formed and existing ties dissolve, giving rise to co‐opetition dynamics at the network level. Taking a configurational approach, we employ the inter‐related dimensions of ties between firm, firm‐level task, network‐level objective, and governance to specify four practical supply network archetypes that cover a wide range of economic activities. We then explain how coopetitive relationships may evolve in these supply network archetypes. Specifically, we discuss how relationships form or dissolve in these archetypes and how local structural changes lead to co‐opetition dynamics at the network level. We also discuss the implications of such dynamics from a managerial perspective.